Left ventricular dysfunction by strain echocardiography in thalassemia patients: a pilot study - Bafna, Akshay Ashok; Shah, Hetan C. (International Journal of Research in Medical Sciences, 2019)
Background: To evaluate the myocardial function and its correlation with serum ferritin and the number of transfusions in beta-thalassemia major patients by using standard echocardiography and left ventricular strain imaging. Methods: This was a cross-sectional exploration study comprised of 56 beta-thalassemia patients conducted at a tertiary-care center in India between September 2016 and August 2017. Patients with age less than 18 years, diagnosed with thalassemia major, recipients of >20 units of blood transfusions, and normal Left Ventricular (LV) function by 2D-echocardiography were included in the study. Severity of iron overload was determined by using serum ferritin levels and LV strain imaging parameters were evaluated by using strain values of 17 LV segments. Results: A total of 56 beta-thalassemia patients were included in the study. Of these, 29(51.8%) patients were boys and 27(48.2%) patients were girls with a mean age of 7.8±1.84 years. Average serum ferritin level was found to be 4089.83 ng/dl. Strain values of the basal lateral wall of the left ventricle were significantly abnormal in patients who received more (>80) transfusions compared with those who received lesser transfusions (p=0.025 and p=0.045), respectively. Patients with serum ferritin >6000 ng/ml had impaired strain (p=0.03). Conclusions: Conventional echocardiographic parameters and Left Ventricular Ejection Fraction (LVEF) do not provide adequate information about LV dysfunction. Systolic strain index imaging of the LV indicated the presence of early LV systolic dysfunction in patients who received a greater number of blood transfusions and patients with higher serum ferritin levels.